Influence of The Quality of E-Banking Services on Customers’ Continuance Intention: A Study with Special Reference to The Federal Bank Ltd - Joseph, Bindu; Rajan , Dr.T.Y. Ebenezer Paul (International Journal of Accounting and Economics Studies, 2025)
In recent days, customers have found it easy to access electronic banking, also known as E-banking, at any time and from any location, which has grown to be a crucial part of modern banking. The purpose of this research is to determine how federal e-banking clients in the Ernakulam area perceive the influence that the quality of their e-banking services plays on their intention to continue. The study is descriptive in style and collected data from 158 e-banking customers of Federal Bank. The study utilized the convenience sampling approach to gather the main data. The variables such as dependability, promptness, assurance and security, convenience, and ease of use are used for measuring service quality. The dependent variable, Continuance intention, is measured by using five items. The result showed that there is a favourable connection between e-banking quality of service factors and continuance intention.